The Media Image of the Multinational Transcarpathia: The Problems of the Search for Ethnic and Civil Identities - Bidzilya, Yuriy M.; Solomin, Yevhen O.; Tolochko, Nataliia V.; Shapovalova, Halyna V.; Shebeshtian, Yaroslava M. (International Journal of Criminology and Sociology, 2021)
The article is concerned with the media image of Transcarpathia in the light of the formation of ethnic and civil identities of the auditory of Ukraine's westernmost region. The peculiarity of this region as a part of the national information space, lies within the fact that the local mass media satisfy the information needs not only in Ukrainian, but also in Hungarian, Romanian, Russian, Romani, German, Slovak, and other languages. At the same time while residing in the borderland area and speaking several languages, the Transcarpathian audience has free access to any media product of the four neighboring EU countries. The broad palette of national and non-national media is called to facilitate the formation of the Transcarpathians' affiliation not only to their ethnic group, but also to the civil (national) identity. To the author's mind, however, an intentional separatist image of the region is emerging due to the destructive materials, the spreading of information myths both in Ukrainian and foreign mass media. The resolution of these problems is seen by the author in the creation of a distinct media system and development of a national information strategy in Ukraine and in the multi-ethnic borderland areas among others.